Evolutions of the Economical Sectors in Brazil in the years of 1992,1995,1999 and 2000: an input-output analysis - Vieira, Fábio Lopes; Shikida, Pery Francisco Assis (Review of Business Management, 2007)
Using input-output analysis this paper presents for 1992, 1995, 1999 and 2000 a comparative analysis of the Brazilian economics sections in the period. As result, it was verified that the domain of the inter-sector relationships in the Brazilian economy was of the sections Metallurgy of iron and steel and Chemistry, corroborated by the tradition of the influence field concept. Key-words: Input-output. Economics sections. Brazil.